Metabolic profiling and transcriptome analysis of Sinomenium acutum provide insights into the biosynthesis of structurally diverse benzylisoquinoline alkaloids - Xiuyu Liu; Jicong Chen; Rui Ma; Le Zhao; Conglong Lian; Suiqing Chen; Ying Ma (Scientific Reports)
Abstract Sinomenium acutum, a traditional medicinal plant, has been utilized for millennia to alleviate various forms of rheumatic pain symptoms. The structurally diverse benzylisoquinoline alkaloids (BIAs) found in S. acutum are the primary contributors to its therapeutic efficacy, with sinomenine being the principal bioactive constituent. In this study, we employed an integrated transcriptomic and metabolomic approach to investigate BIA biosynthesis in S. acutum. Transcriptome sequencing, functional annotation, and differential gene expression analysis were combined with metabolite profiling to predict biosynthetic pathways of structurally diverse BIAs and screen candidate genes. Metabolomic analysis revealed significant stem-enriched accumulation of BIAs compared to leaves. Furthermore, we proposed a biosynthetic pathway of sinomenine and hypothesized that 34 key candidate genes, including cytochrome P450 (CYP450s), reductases, 2-oxoglutarate-dependent dioxygenases (2-ODDs), and O-methyltransferases (O-MTs), might be involved in its biosynthetic process. This study provides a foundation for understanding the biosynthesis of structurally diverse BIA compounds in S. acutum and offers critical insights for future characterization of functional genetic elements.